A survey of SiC power MOSFETs short-circuit robustness and failure mode analysis. (September 2017) - Ceccarelli, L.; Reigosa, P.D.; Iannuzzo, F.; Blaabjerg, F.
Abstract: The aim of this paper is to provide an extensive overview about the state-of-art commercially available SiC power MOSFET, focusing on their short-circuit ruggedness. A detailed literature investigation has been carried out, in order to collect and understand the latest research contribution within this topic and create a survey of the present scenario of SiC MOSFETs reliability evaluation and failure mode analysis, pointing out the evolution and improvements as well as the future challenges in this promising device technology. Highlights: An overview of the short-circuit ruggedness of commercially-available SiC MOSFETs is provided. The most common failure mechanisms have been spotted and investigated. Experimental waveforms show the short-circuit behavior for both discrete devices and power modules. The present modeling activity and perspective technology improvements are pointed out.